Analisis Naratif Perempuan Madura dalam Bahan Ajar Bahasa Madura (Faculty of Communications Science, Dr. Soetomo University, 2018)
How to preserve culture is to be taught and taught as early as possible to the next generation.The most important period in cultural absorption is adolescence, so it is necessary to involve culture in formal education. Women are important to examine, because women have many rules in her living. As a